Aligning sociopolitical thrusts for local development management in Barangay Cabitan, Mandaon, Masbate - Oppus, Pamela G. (1999)
Convergence takes on various modes. In Barangay Cabitan, convergence was manifested in plans which shared the congruence of activities for common targets as well as pooled resources for agreed targets. The case draws insights from the realities of managing and achieving convergence. In its pursuit, aligning political thrusts emerges as key in defining a local development agenda and pooling resources for its implementation. Here, the outlook of the leader performs a significant role.
Keywords: Basic needs -- Case studies -- Masbate; Capacity building; Comprehensive and Integrated Delivery of Social Services (CIDSS); Integrated Approach to Local Development and Management (IALDM); Minimum Basic Needs (MBN) Approach; Social Reform Agenda (SRA)